Water-resistant and high-temperature-resistant coated blasting bead and preparation method thereof

By using polymer materials such as zein, HPMC and EC as coating wall materials, and combined with plasticizers and anti-adhesive agents, the problem of insufficient water resistance and high temperature resistance of explosive beads in humid environments and high temperature conditions is solved, and higher water resistance and high temperature resistance are achieved, extending the shelf life of the product and improving safety.

CN119908466APending Publication Date: 2025-05-02GUANGDONG PHARMA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510219104.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing explosive beads have problems with insufficient water resistance and high temperature resistance under humid environments and high temperature conditions, resulting in swelling, rupture of rubber materials and leakage of internal contents, affecting the product's shelf life and consumer experience.

Method used

The polymer coating materials zein, hydroxypropyl methyl cellulose (HPMC) and ethyl cellulose (EC) are used as the coating wall materials, and plasticizers and anti-adhesives are added to coat them through fluidized bed coating method to optimize process parameters to improve the coating effect.

Benefits of technology

It significantly improves the water resistance and high temperature resistance of the coated explosive beads, ensures that the coating layer maintains integrity and stability in humid environments and high temperature conditions, extends the shelf life of the product and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119908466A_ABST
    Figure CN119908466A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of food and biological medicine health, and relates to a water-resistant and high-temperature-resistant coated blasting bead and a preparation method thereof. The coating wall material of the coated blasting bead comprises the polymer coating material, the plasticizer and the anti-sticking agent, the blasting bead body is coated through a Glatt fluidized bed, the prepared coated blasting bead has excellent water resistance and high temperature resistance, and the taste and blasting feeling are not affected under high-temperature and high-humidity conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of food and biomedical health technology, and in particular to a water-resistant and high-temperature-resistant coated explosive bead and a preparation method thereof. Background Art

[0002] With the rapid development of food, tobacco, daily chemical products and other fields, the market demand for popping beads, as an innovative product that combines taste experience with functional release, is growing. However, the existing popping beads have significant technical bottlenecks when dealing with complex environments, especially the problems of insufficient water resistance and high temperature resistance are particularly prominent. In a humid environment, if the rubber material of the popping beads is a hydrophilic polymer, it is easy to absorb moisture. For example, when gelatin is used as a wrapping material, the gelatin molecules contain a large number of hydrophilic groups (such as amino and carboxyl groups). These groups will form hydrogen bonds with water molecules, causing water molecules to easily enter the interior of the popping beads. When a large amount of water enters, the rubber material will swell, eventually causing the popping beads to rupture. Secondly, many rubber materials may have tiny pores or defects, and water molecules can penetrate through these pores, causing the beads to lose their bursting properties or even break and leak the internal contents, affecting the shelf life of the product and consumer experience; under high temperature conditions, the thermal stability of the rubber material of the beads is poor. Under high temperature conditions, the thermal motion of its molecules is intensified, and the intermolecular forces are weakened, resulting in softening and deformation, losing the bursting feeling or losing the ability to effectively wrap the internal substances. When the temperature rises further, the beads may break due to excessive deformation of the material. The liquid or filler inside the beads and the rubber material may have different thermal expansion coefficients. When the internal liquid expands more than the rubber material due to heat, it will exert greater pressure on the rubber. Once it exceeds the limit that the rubber can withstand, it will cause the beads to break. In addition, if the rubber material is some polymer material or volatile components, hydrolysis or thermal decomposition reactions may occur at high temperatures, resulting in the instability of the rubber structure, which in turn causes the softening of the beads and the loss of the bursting feeling or directly causes the beads to break. This further reduces the practicality and safety of the product. Therefore, developing a coated explosive bead that is both water-resistant and high-temperature resistant has become a technical problem that the industry needs to solve urgently.

[0003] Coating technology can usually provide a protective layer for the popping beads to prevent moisture from entering and reduce the impact of the external environment on the internal. The coating layer can prevent moisture absorption and reduce internal pressure changes, thereby improving the moisture resistance of the popping beads. At the same time, it can also provide certain thermal protection, slow down the impact of high temperature on the shell material of the popping beads, and enhance its high temperature resistance. Zein (corn gluten) is a protein extracted from corn, which is usually used in food, cosmetics and other fields because it has good biocompatibility, plasticity, water resistance and thermal stability. Zein has good adhesion and can evenly cover the surface of the popping beads to form a protective film to prevent moisture from entering. At the same time, it can also remain stable at high temperatures to prevent material deformation or decomposition. At the same time, zein is a bio-based polymer material that is environmentally friendly and degradable, meeting the needs of sustainable development. Therefore, it is a suitable coating material for popping beads. In addition, process optimization is also a focus. How to improve the coating effect by adjusting process parameters such as temperature, dosage, and concentration of coating materials is also an urgent problem that needs to be solved. Summary of the invention

[0004] The purpose of the present invention is to provide a water-resistant and high-temperature-resistant coated explosive bead and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a water-resistant and high-temperature-resistant coated popping bead, comprising a popping bead body and a coating wall material, wherein the coating wall material comprises: a polymer coating material, a plasticizer and an anti-sticking agent.

[0007] Furthermore, the polymer coating material includes one of zein, hydroxypropyl methylcellulose (HPMC) and ethyl cellulose (EC).

[0008] Furthermore, the plasticizer includes at least one of triethyl citrate, epoxidized soybean oil, citrate, epoxidized linseed oil, fatty acid salts, aliphatic polyesters, triacetin, polyethylene glycol, propylene glycol and glycerol.

[0009] Furthermore, the anti-adhesive agent includes at least one of talc, magnesium stearate, microcrystalline cellulose and silicon dioxide.

[0010] Furthermore, the mass ratio of the polymer coating material, the plasticizer and the anti-sticking agent in the coating wall material is 6:1:1.5.

[0011] The second technical solution of the present invention is to provide a method for preparing the above-mentioned water-resistant and high-temperature-resistant coated explosive beads, the steps comprising:

[0012] The polymer coating material, the plasticizer and the anti-sticking agent are mixed with the solvent and then preheated to obtain a coating solution;

[0013] Then, the coating liquid is used to coat the popping bead body by a fluidized bed coating method, so as to obtain the water-resistant and high-temperature-resistant coated popping bead.

[0014] Furthermore, the mass ratio of the sum of the mass of the polymer coating material, the plasticizer and the anti-sticking agent to the mass of the solvent is 8.5:91.5.

[0015] Furthermore, the solvent consists of water and ethanol in a mass ratio of 21.5:70.

[0016] Furthermore, the preheating temperature is 55°C.

[0017] Furthermore, the atomization pressure of the fluidized bed coating is 0.51 bar, the wind pressure is 0.45 bar, and the flow rate is 0.5 mL / min.

[0018] The present invention discloses the following technical effects:

[0019] The present invention enhances the compactness and hydrophobicity of the coating layer by adding an appropriate amount of plasticizer to the polymer coating material, effectively preventing the penetration of water molecules, thereby greatly improving the water resistance of the coated beads. Even in a humid environment, the integrity and stability of the coating layer can be maintained, thereby extending the shelf life of the product.

[0020] The selection of polymer coating materials and the reasonable proportion of plasticizers and anti-adherents in the present invention enable the coating layer to maintain good structural stability and thermal resistance under high temperature conditions, effectively preventing the coating layer from softening, deforming and melting. This feature enables the coated beads to be used in a wider temperature range, improving the adaptability and safety of the product.

[0021] The present invention adopts a fluidized bed for coating, and combines specific preheating temperature, solvent ratio, atomization pressure, wind pressure, flow rate and other parameter settings to achieve uniform spraying and rapid solidification of the coating liquid, ensuring the uniformity and consistency of the coating layer. At the same time, the preparation method is simple to operate, easy to control, and is conducive to industrial production.

[0022] The hydroxypropyl methylcellulose (HPMC) used in the coating material of the present invention has a suitable molecular weight and molecular structure, and the molecular chains can be mutually entangled and cross-linked, and can form a continuous and uniform film on the surface of the material. In addition, HPMC can swell in water and form a solution with a certain viscosity. After dissolution, it can form a protective film on the surface of the food, and the concentration can be adjusted as needed to control the thickness and performance of the film. Under different temperature and pH conditions, its solubility is also relatively stable. For the human body, HPMC is a biocompatible material, and will not cause the human body's immune response or other harmful physiological reactions after entering the human body.

[0023] The zein used in the coating material of the present invention is a natural biomacromolecule that can be decomposed by microorganisms in the natural environment. Compared with some synthetic polymer materials, it will not remain in the environment for a long time like materials such as plastics, causing "white pollution". Zein is extracted from corn, which is a widely planted crop with abundant and renewable sources. This is in contrast to synthetic materials that rely on non-renewable resources such as petroleum, and has great advantages in sustainable resource utilization. Moreover, the cultivation of corn can be continuously obtained through agricultural production, ensuring a stable supply of materials. Zein is used as a blasting bead coating material because it can form a film with good barrier properties, which can effectively block the penetration of small molecules such as oxygen and moisture. The good film-forming and solubility of HPMC can complement the barrier properties and biodegradability of zein, further enhancing the temperature and water resistance and stability of the coating.

[0024] The present invention successfully solves the problems of existing coated beads being not resistant to water and high temperatures through innovative coating wall material formula and optimized preparation process, improves product performance stability and market competitiveness, and provides strong technical support for the development of related industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is a photo of the coated burst beads prepared in Example 1;

[0027] Figure 2 The actual picture of the coated popping beads prepared in Example 2, wherein the left side shows the popping beads coated with 75 mL of coating solution, and the right side shows the popping beads coated with 100 mL of coating solution;

[0028] Figure 3 This is a physical picture of the coated popping beads prepared in Example 2 after being treated with 80°C hot water, wherein the left side shows the popping beads coated with 75mL of coating solution, and the right side shows the popping beads coated with 100mL of coating solution.

[0029] Figure 4 The coated beads were prepared in Example 3. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0035] The popping bead bodies used in the specific implementation scheme of the present invention are commercially available Nansha sweet orange popping bead bodies. The use of other types of popping bead bodies will not affect the technical effects of the present invention.

[0036] Usually, the rubber for popping beads on the market is mostly made of thermosensitive gelatin, hydrophilic glue, etc. as the coating agent, and has poor thermal stability. When in a high temperature environment, the rubber for popping beads will become soft and may stick to each other, which will not only affect the appearance, but also the taste and popping feeling of the popping beads themselves. Rubber materials such as gelatin, hydrophilic colloids and sugar alcohols have extremely strong water absorption and moisture absorption properties. In a high humidity environment, the rubber will absorb moisture quickly and its mechanical strength will decrease significantly. For example, in the humid southern region or the rainy season, the rubber for popping beads may become too soft due to absorbing too much water, which will also affect the taste and popping feeling of the popping beads.

[0037] Example 1

[0038] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0039] S1. Prepare coating materials EN-10 (ethyl cellulose), 95% ethanol, and water in a mass ratio of 10:315:75 and set aside;

[0040] S2, dilute ethanol with water to a concentration of 90%, then add EN-10 and dissolve it at 400 rpm to obtain;

[0041] S3, coating the commercially available popping pearls (Nansha white peach popping pearls) with 30 mL of coating liquid using a Glatt fluidized bed;

[0042] The fluidized bed coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0043] Example 2

[0044] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0045] S1. Prepare coating materials EC (ethyl cellulose), triethyl citrate (TEC), magnesium stearate, ethanol and water in a mass ratio of 2.5:1:0.5:91.2:4.9 respectively for later use;

[0046] S2, dissolving EC in ethanol, then adding the prescribed amount of triethyl citrate (TEC) and magnesium stearate, stirring at 400 rpm to dissolve, to obtain;

[0047] S3, coating the commercially available popping beads (350 Nansha sweet orange popping beads) with the coating solution (75 mL or 100 mL) using a Glatt fluidized bed;

[0048] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0049] Example 3

[0050] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0051] S1. Prepare polymer coating material (corn protein), triethyl citrate (TEC), anti-sticking agent (magnesium stearate), ethanol and water in a mass ratio of 8:2:0.5:70:19.5 and set aside;

[0052] S2. Dilute anhydrous ethanol with 10% water to a concentration of 87.5%, then add corn protein, and stir at 400 rpm until most of the polymer coating material is dissolved, then add the remaining 9.5% water, stir until the polymer coating material is completely dissolved, and finally add triethyl citrate (TEC) and anti-sticking agent (magnesium stearate), stir evenly to obtain a coating solution;

[0053] S3, preheat the coating liquid to 55°C, and then coat the popping beads (350 Nansha sweet orange popping beads) using a Glatt fluidized bed, with a coating liquid dosage of 50 ml;

[0054] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0055] Example 4

[0056] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0057] S1. Prepare corn protein, triethyl citrate (TEC), anti-adhesive agent (talc), ethanol and water in a mass ratio of 6:1:1.5:70:21.5 and set aside;

[0058] S2, dilute ethanol with water to a concentration of 90%, then add corn protein, and stir at 400 rpm until most of the polymer coating material is dissolved, then add the remaining water, stir until the polymer coating material is completely dissolved, and finally add triethyl citrate (TEC) and anti-sticking agent (talc), stir evenly to obtain a coating solution;

[0059] S3, preheat the coating solution to 55°C, and then coat the commercially available popping beads (350 Nansha sweet orange popping beads) with 75 mL of the coating solution using a Glatt fluidized bed;

[0060] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0061] Example 5

[0062] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0063] S1. Prepare hydroxypropyl methylcellulose, triethyl citrate (TEC), ethanol and water in a mass ratio of 2:0.8:70:27.2 for later use;

[0064] S2, diluting ethanol with water to a concentration of 70%, then adding hydroxypropyl methylcellulose, and stirring at 400 rpm until dissolved, and finally adding triethyl citrate (TEC), stirring evenly to obtain coating solution 1;

[0065] S3. Prepare corn protein, triethyl citrate (TEC), anti-adhesive agent (talc), ethanol and water in a mass ratio of 5:0.8:1.5:70:22.7 for later use;

[0066] S4, dilute ethanol with 10% water to a concentration of 87.5%, then add corn gluten, and stir at 400 rpm until most of it is dissolved, then add the remaining water, stir until it is completely dissolved, and finally add triethyl citrate (TEC) and an anti-sticking agent (talc), stir evenly to obtain coating solution 2;

[0067] S4. Use Glatt fluidized bed to coat the commercially available popping beads (350 Nansha sweet orange popping beads) with coating liquid 1 for 5 minutes; then use coating liquid 2 for further coating, and the amount of coating liquid 2 used is 75 mL.

[0068] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0069] Example 6

[0070] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0071] S1. Prepare corn protein, triethyl citrate (TEC), anti-adhesive agent (talc), ethanol, and water in a mass ratio of 6:0.8:1.5:70:21.7; prepare chitosan, glacial acetic acid, talc, and water in a mass ratio of 0.5:1:2.5:96 and set aside;

[0072] S2, dilute ethanol with water to a concentration of 70%, add hydroxypropyl methylcellulose, dissolve, add triethyl citrate (TEC), stir evenly to obtain coating solution 1; dilute ethanol with water to a concentration of 70%, then add corn protein, stir at 400 rpm to dissolve, finally add triethyl citrate (TEC) and anti-sticking agent (talcum powder), stir evenly to obtain coating solution 2; add glacial acetic acid to pure water to adjust the pH, add chitosan and stir at 400 rpm until dissolved, finally add talcum powder and stir evenly to obtain coating solution 3;

[0073] S3, using Glatt fluidized bed to first use coating solution 1 to coat the commercially available popping beads (350 Nansha sweet orange popping beads) for the first layer of coating, the coating time is 5 minutes; then change to coating solution 2 (75 mL) for the second layer of coating; finally use coating solution 3 (45 mL) for the third layer of coating;

[0074] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0075] Example 7

[0076] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0077] S1. Prepare hydroxypropyl methylcellulose, triethyl citrate (TEC), ethanol, and water in a mass ratio of 2:0.8:70:27.2; prepare polymer coating material (corn protein), triethyl citrate (TEC), anti-adhesive agent (talcum powder), ethanol, and water in a mass ratio of 6:0.8:1.5:70:21.7; prepare chitosan, glacial acetic acid, talcum powder, and water in a mass ratio of 0.5:1:2.5:96 and set aside;

[0078] S2, dilute ethanol with water to a concentration of 70%, then add hydroxypropyl methylcellulose, stir at 400 rpm until dissolved, finally add triethyl citrate (TEC), stir evenly to obtain coating solution 1; dilute ethanol with water to a concentration of 70%, then add corn protein, stir at 400 rpm until completely dissolved, finally add triethyl citrate (TEC) and anti-sticking agent (talcum powder), stir evenly to obtain coating solution 2, add glacial acetic acid to pure water to adjust the pH, add chitosan and stir at 400 rpm until dissolved, finally add talcum powder and stir evenly to obtain coating solution 3;

[0079] S3, using a Glatt fluidized bed, firstly coat the commercially available popping pearls (350 Nansha sweet orange popping pearls) with coating liquid 1 for 5 min; then coat the second layer with coating liquid 2 (75 mL); finally, coat the third layer with coating liquid 3 (45 mL);

[0080] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0081] Comparative Example 1

[0082] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0083] S1. Prepare coating materials EC, triethyl citrate (TEC), magnesium stearate, and 95% ethanol in a mass ratio of 3:1.5:0.5:95 respectively for later use;

[0084] S2, dissolving EC in 95% ethanol, then adding the prescribed amount of triethyl citrate (TEC) and magnesium stearate, and dissolving them at 400 rpm to obtain;

[0085] S3, using Glatt fluidized bed to coat the popping beads (350 Nansha sweet orange popping beads), the amount of coating liquid used was 75mL and 100mL respectively;

[0086] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0087] Comparative Example 2

[0088] The preparation steps of coated burst beads are as follows:

[0089] S1. Prepare hydroxypropyl methylcellulose, triethyl citrate (TEC), ethanol and water in a mass ratio of 2:0.6:70:27.6 for later use;

[0090] S2, dilute ethanol with water to a concentration of 90%, then add hydroxypropyl methylcellulose, and stir at 400 rpm until dissolved, and finally add triethyl citrate (TEC), stir evenly to obtain a coating solution;

[0091] S3, preheat the coating solution to 40-50°C, and then use a coating pan to coat 25g of popping beads (Nansha sweet orange popping beads) with 20mL of coating solution;

[0092] The fan speed of the coating pot is 1800rpm, the inlet air temperature is 48-50℃, the atomization pressure is 0.11MPa-0.13MPa, the outlet air temperature is 45-48℃, the peristaltic pump speed is 3rpm, and the main engine speed is 5rpm.

[0093] Comparative Example 3

[0094] The preparation steps of coated burst beads are as follows:

[0095] S1. Prepare polymer coating material (corn protein), triethyl citrate (TEC), anti-adhesive agent (talc), ethanol and water in a mass ratio of 6:1.5:1.5:70:21 and set aside;

[0096] S2, dilute ethanol with 10% water to a concentration of 87.5%, then add corn gluten, and stir at 400 rpm until most of it is dissolved, then add the remaining water, stir until the corn gluten is completely dissolved, and finally add triethyl citrate (TEC) and an anti-sticking agent (talc), stir evenly to obtain a coating solution;

[0097] S3, preheat the coating solution to 40-50°C, and then use a coating pan to coat the popping beads (25 g of Nansha sweet orange popping beads) with the coating solution (100 mL);

[0098] The fan speed of the coating pot is 1800rpm, the inlet air temperature is 48-50℃, the atomization pressure is 0.11MPa-0.13MPa, the outlet air temperature is 45-48℃, the peristaltic pump speed is 3rpm, and the main engine speed is 5rpm.

[0099] Comparative Example 4

[0100] The preparation steps of coated burst beads are as follows:

[0101] S1. Prepare chitosan, anti-adhesive agent (talc), glacial acetic acid, triethyl citrate (TEC) and water in a mass ratio of 0.5:1.5:1:0.13:96 and set aside;

[0102] S2. After mixing glacial acetic acid and water evenly, slowly add chitosan while stirring, add talcum powder and triethyl citrate after stirring evenly, and mix well to obtain a coating solution;

[0103] S3, preheat the coating solution to 40-50°C, and then use a coating pan to coat the popping beads (25 g of Nansha sweet orange popping beads) with the coating solution (60 mL);

[0104] The fan speed of the coating pot is 1800rpm, the inlet air temperature is 48-50℃, the atomization pressure is 0.11MPa-0.13MPa, the outlet air temperature is 45-48℃, the peristaltic pump speed is 2rpm, and the main engine speed is 5rpm.

[0105] In the preparation of coated popping beads in Comparative Examples 1 to 3, the materials easily fly out of the coating pot during the coating process, resulting in large losses. There are pinhole-sized holes on the coated popping beads, and the spray gun of Comparative Example 3 is easily clogged, resulting in uneven spraying of liquid. The popping beads are prone to softening during the coating process.

[0106] Comparative Example 5

[0107] Compared with Example 4, the only difference is that the mass ratio of zein, triethyl citrate (TEC), anti-adherent (talc), ethanol and water in step S1 is 8:0.5:1:70:20.5.

[0108] Comparative Example 6

[0109] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0110] S1. Prepare corn protein, triethyl citrate (TEC), anti-adhesive agent (talcum powder), ethanol, and water in a mass ratio of 5:0.8:1.5:70:22.7; prepare chitosan, glacial acetic acid, talcum powder, and water in a mass ratio of 0.5:1:2.5:96 and set aside;

[0111] S2, dilute ethanol with 10% water to a concentration of 87.5%, then add corn protein, stir at 400 rpm to completely dissolve, finally add triethyl citrate (TEC) and anti-sticking agent (talcum powder), stir evenly to obtain coating solution 2, add glacial acetic acid to pure water to adjust the pH, add chitosan and stir at 400 rpm until dissolved, finally add talcum powder and stir evenly to obtain coating solution 3;

[0112] S3, using Glatt fluidized bed to coat the commercially available popping pearls (350 Nansha sweet orange popping pearls) with coating solution 2 (75 mL) for the first layer; then coating solution 3 (45 mL) for the second layer;

[0113] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0114] Comparative Example 7

[0115] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0116] S1. Prepare corn protein, triethyl citrate (TEC), anti-adhesive agent (talcum powder), ethanol, and water in a mass ratio of 7:0.8:1.5:70:20.7; prepare chitosan, glacial acetic acid, talcum powder, and water in a mass ratio of 0.5:1:2.5:96 and set aside;

[0117] S2, dilute ethanol with water to a concentration of 70%, then add corn protein, and stir at 400 rpm until it is completely dissolved, finally add triethyl citrate (TEC) and anti-sticking agent (talcum powder), stir evenly to obtain coating solution 2, add glacial acetic acid to pure water to adjust the pH, add chitosan and stir at 400 rpm until it is dissolved, finally add talcum powder and stir evenly to obtain coating solution 3;

[0118] S3, using Glatt fluidized bed to coat the commercially available popping pearls (350 Nansha sweet orange popping pearls) with coating solution 2 (75 mL) for the first layer; then coating solution 3 (45 mL) for the second layer;

[0119] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0120] After 15 minutes of coating, the coating became sticky and could not be successfully coated.

[0121] Comparative Example 8

[0122] The preparation steps of coated burst beads are as follows:

[0123] S1. Prepare coating materials including corn protein, triethyl citrate (TEC), magnesium stearate, ethanol and water in a mass ratio of 8:2:0.5:70:19.5 and set aside;

[0124] S2, dilute ethanol with water to a concentration of 90%, then add corn protein, and stir at 400 rpm until most of the polymer coating material is dissolved, then add the remaining water, stir until all dissolved, and finally add triethyl citrate (TEC) and magnesium stearate, stir evenly to obtain a coating solution;

[0125] S3, preheating the coating solution to 55°C, and then coating the commercially available popping beads (350 Nansha sweet orange popping beads) with the coating solution (75 mL) using a Glatt fluidized bed;

[0126] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0127] Comparative Example 9

[0128] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0129] S1. Prepare hydroxypropyl methylcellulose, triethyl citrate (TEC), ethanol, and water in a mass ratio of 2:0.8:70:27.2; prepare polymer coating material (corn protein), triethyl citrate (TEC), anti-adhesive agent (talcum powder), ethanol, and water in a mass ratio of 6:0.8:1.5:70:21.7; prepare chitosan, glacial acetic acid, talcum powder, and water in a mass ratio of 0.5:1:2.5:96 and set aside;

[0130] S2, dilute ethanol with water to a concentration of 70%, then add hydroxypropyl methylcellulose, stir the material at 400 rpm to dissolve, finally add triethyl citrate (TEC), stir evenly to obtain coating solution 1; dilute ethanol with water to a concentration of 70%, then add corn protein, stir at 400 rpm to completely dissolve, finally add triethyl citrate (TEC) and anti-sticking agent (talcum powder), stir evenly to obtain coating solution 2, add glacial acetic acid to pure water to adjust the pH, add chitosan and stir at 400 rpm until dissolved, finally add talcum powder and stir evenly to obtain coating solution 3;

[0131] S3, using Glatt fluidized bed to coat the commercially available popping pearls (350 Nansha sweet orange popping pearls) with coating liquid 1 for 5 min; then coating liquid 2 (55 mL) for the second layer; finally coating liquid 3 (45 mL) for the third layer;

[0132] The coating atomization pressure was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.

[0133] Comparative Example 10

[0134] The preparation steps of water-resistant and high temperature-resistant coated explosive beads are as follows:

[0135] S1. Prepare hydroxypropyl methylcellulose, triethyl citrate (TEC), ethanol, and water in a mass ratio of 2:0.8:70:27.2; prepare zein, triethyl citrate (TEC), anti-adhesive agent (talcum powder), ethanol, and water in a mass ratio of 6:0.8:1.5:70:21.7; prepare chitosan, glacial acetic acid, talcum powder, and water in a mass ratio of 0.5:1:2.5:96 and set aside;

[0136] S2, dilute ethanol with water to a concentration of 70%, then add hydroxypropyl methylcellulose, stir at 400 rpm until dissolved, finally add triethyl citrate (TEC), stir evenly to obtain coating solution 1; dilute ethanol with water to a concentration of 70%, then add corn protein, stir at 400 rpm until completely dissolved, finally add triethyl citrate (TEC) and anti-sticking agent (talcum powder), stir evenly to obtain coating solution 2, add glacial acetic acid to pure water to adjust the pH, add chitosan and stir at 400 rpm until dissolved, finally add talcum powder and stir evenly to obtain coating solution 3;

[0137] S3, using Glatt fluidized bed to coat the commercially available popping pearls (350 Nansha sweet orange popping pearls) with coating liquid 1 for 5 min; then coating liquid 2 (65 mL) for the second layer; finally coating liquid 3 (45 mL) for the third layer;

[0138] The atomization pressure of the Glatt fluidized bed coating method is 0.51 bar, the wind pressure is 0.45 bar, and the flow rate is 0.5 mL / min.

[0139] Test example

[0140] The coated popping beads prepared in Examples 1-7 and Comparative Examples 1 to 10 were placed in an oven at 80°C and 100°C (on baking paper) and hot water, respectively, and the appearance changes were observed for 10 min, 20 min, 30 min and 60 min. The results are shown in Table 1.

[0141] Table 1

[0142]

[0143]

[0144]

[0145]

[0146]

[0147] The coated bursting beads prepared in Comparative Example 4 had many pores in hot water, which led to rupture. The surface of the coating became brighter in the oven, and oil stains appeared on the surface of the baking paper.

[0148] In Example 7, a Glatt fluidized bed was used to first apply a first layer of coating to commercially available popping beads (Nansha sweet orange popping beads) using coating liquid 1 (5 min); then a second layer of coating was applied using coating liquid 2 (75 mL); and finally a third layer of coating was applied using coating liquid 3. The coated popping beads had good water and high temperature resistance.

[0149] Figure 1 This is a real picture of the coated burst beads prepared in Example 1.

[0150] Figure 2 This is a real picture of the coated popping beads prepared in Example 2, wherein the left side shows the popping beads coated with 75 mL of coating liquid, and the right side shows the popping beads coated with 100 mL of coating liquid.

[0151] Figure 3 This is a physical picture of the coated popping beads prepared in Example 2 after being treated with 80°C hot water, wherein the left side shows the popping beads coated with 75mL of coating solution, and the right side shows the popping beads coated with 100mL of coating solution.

[0152] Figure 4 The coated beads were prepared in Example 3.

[0153] Gummy Candy Experiment

[0154] The capsule bursting beads prepared in Example 7 were stuffed into fruit juice jelly (high water content) and vitamin C jelly (low water content) respectively, and placed in a 40°C oven for 3 months. During the cooling of the jelly, the bursting beads were checked for rupture and whether there was still a sense of rupture. The results are shown in Table 2.

[0155] Table 2

[0156]

[0157] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A water-resistant and high-temperature-resistant coated popping bead, comprising a popping bead body and a coating wall material, characterized in that: The coating wall material comprises: a polymer coating material, a plasticizer and an anti-sticking agent.

2. The water-resistant and high-temperature-resistant coated explosive beads according to claim 1, characterized in that: The polymer coating material includes one of corn protein, hydroxypropyl methylcellulose and ethyl cellulose; and / or the plasticizer includes at least one of triethyl citrate, epoxidized soybean oil, citrate, epoxidized linseed oil, fatty acid salt, aliphatic polyester, triacetin, polyethylene glycol, propylene glycol and glycerol.

3. The water-resistant and high-temperature-resistant coated explosive beads according to claim 1, characterized in that: The anti-adherent agent includes at least one of talc, magnesium stearate, microcrystalline cellulose and silicon dioxide.

4. The water-resistant and high-temperature-resistant coated explosive beads according to claim 1, characterized in that: The mass ratio of the polymer coating material, the plasticizer and the anti-sticking agent in the coating wall material is 6:1:1.

5.

5. A method for preparing water-resistant and high-temperature-resistant coated explosive beads according to any one of claims 1 to 4, characterized in that the steps include: The polymer coating material, the plasticizer and the anti-sticking agent are mixed with the solvent and then preheated to obtain a coating solution; Then, the coating liquid is used to coat the popping bead body by a fluidized bed coating method, so as to obtain the water-resistant and high-temperature-resistant coated popping bead.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the sum of the mass of the polymer coating material, triethyl citrate and the anti-sticking agent to the mass of the solvent is 8.5:91.

5.

7. The preparation method according to claim 5, characterized in that: The solvent consists of water and ethanol in a mass ratio of 21.5:

70.

8. The preparation method according to claim 5, characterized in that: The preheating temperature is 55°C.

9. The preparation method according to claim 5, characterized in that: The atomization pressure of the fluidized bed coating was 0.51 bar, the wind pressure was 0.45 bar, and the flow rate was 0.5 mL / min.